Comparison of Optic Disc on Machine (OCT) Versus Manual Assessment on Slit Lamp - Dr. Vatsala Vats,; Dr. Priyanka Gupta,; Dr. Mohd. Ghainual Hasan,; Dr. Ashish Kundu,; Dr. Shivani Raturi, (British Journal of Healthcare and Medical Research, 2023)
Background and Objectives: OCT is an evolving tool of diagnosing various anatomical anomalies of eye specially for retinal parameters and also gaining a strong role in other structures like cornea, angle, optic disc. But its cost and incorporation of newer technology with time becomes a dilemma for its purchase. The subjective assessment of optic nerve head (ONH) with the help of 90 dioptre, or 78 dioptre lens on slit lamp, or direct ophthalmoscope are methods in common clinical practice in most ophthalmic settings. Such manual assessment forms the core of the strategic approach to diagnose optic disc variations. This study aimed to learn if objective tool like OCT could do away the subjective method. Material and Method: All eyes underwent comprehensive ophthalmic evaluation including visual acuity, slit lamp biomicroscopy, tonometry, and OCT. The optic disc was assessed on slit lamp by 78 D as the morphology appeared close to natural dimensions. Disc size, NRR, C:D ratio noted on OCT were compared with the readings of manual method. Study Design: A cross sectional, hospital based, prospective study involving 200 eyes of 100 patients. Result: In our study, we found that the size was significantly more on OCT than manual assessment on slit lamp with 78 dioptre lens. Glaucoma Suspect eyes on slit lamp were found to have suspicious discs even on OCT in almost 90% eyes. Interpretation & Conclusion: Subjective assessment is mandatory for diagnostic purposes as it is vivid, and is easily available on account of low cost. OCT is additive of information of structures not visible to human eye directly. A proper combination of OCT and SLB brings specificity and clarity to both the patient and clinician.